Rare case of bilateral complex odontoma associated with mandibular bicuspids - Rangeeth Bollam Nammalwar; Joyson Moses; Sathya Jeeva (Wolters Kluwer Medknow Publications, 2018)
Among oral pathologic lesions, odontomas are the most common odontogenic tumor of the jaws and generally asymptomatic. They are mostly diagnosed as a result of routine radiographic investigation. In this report, we describe a very rare occurrence of bilateral complex odontoma in the region of the mandibular second premolar. Conservative surgical procedure was planned, and removal of the odontomas was carried out through the socket after extraction of the deciduous second molars, and the diagnosis was confirmed with a histopathological study.